2016
DOI: 10.1088/1741-2560/13/3/036017
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous decoding of finger movements from ECoG signals using long-range dependencies conditional random fields

Abstract: The method proposed in this work makes use of probabilistic graphical models to incorporate temporal information in the classification of finger movements from electrocorticographic recordings. The proposed method highlights the importance of including prior information about the task that the subjects execute. As the results show, the combination of these two features effectively produce a significant improvement of the system's classification performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Pistohl et al, Chestek et al, and Wang et al also showed that high classification of gesture types could be obtained from the channels on the postcentral gyrus [ 12 , 15 , 23 ]. It is worth noting that Wang et al managed to decode 3D arm movement with the ECoG signals obtained from the postcentral gyrus of a paralyzed participant, who cannot move his limbs at all [ 24 ]. Therefore, it suggested that the activation of the postcentral gyrus played an influential role in hand movement.…”
Section: Discussionmentioning
confidence: 99%
“…Pistohl et al, Chestek et al, and Wang et al also showed that high classification of gesture types could be obtained from the channels on the postcentral gyrus [ 12 , 15 , 23 ]. It is worth noting that Wang et al managed to decode 3D arm movement with the ECoG signals obtained from the postcentral gyrus of a paralyzed participant, who cannot move his limbs at all [ 24 ]. Therefore, it suggested that the activation of the postcentral gyrus played an influential role in hand movement.…”
Section: Discussionmentioning
confidence: 99%
“…These different frequency bands have been extensively used as features to model brain phenomena [1,2,3,4,5,6,7,8,9,10,11,12]. For instance, LFC usually measured as the raw brain signal low-pass filtered (below 40 Hz) [13,14,15], have been used in many applications, including decoding of position, velocity and acceleration of executed motor tasks [16,17,18,19,20,21,13,14,15] leading to improvements compared to models restricted to amplitude modulations in only the alpha and beta bands [22,19,20]. Given the enhanced signal to noise ratio compared with both EEG and MEG, ECoG can also exploit high-frequency components above 100 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Given the enhanced signal to noise ratio compared with both EEG and MEG, ECoG can also exploit high-frequency components above 100 Hz. High frequency band activity (HFB), usually measured as the averaged power changes in the band from 70 to 200 Hz, has been used for decoding in multiple tasks, including motor, auditory, and visual [16,17,18,19,20]. The extracted features are used to model brain responses for basic brain research, medical diagnostic, and rehabilitation areas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations